Đặc điểm sinh khí hậu vùng Bắc Trung Bộ qua phân tích các biểu đồ khí hậu - Vân, Nguyễn Khanh; Hiền, Nguyễn Thị; Lộc, Phan Kế; Hiệp, Nguyễn Tiến (Vietnam Journal of Earth Sciences, 2000)
Some features of biocllmatic conelitions in NorthernPart of Gentral Region of Viet Nem based onanalyzing of its climatodiagrams